The Impact of Post-Potivism and Constructivism on Public Policy: A review of Philosophy of Science in Indonesia - Retisfa Khairanis; Istiadah Istiadah (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to analyze the impact of the post-positivist and constructivist paradigms on public policy in Indonesia from an academic perspective. The main focus of this research is how the two paradigms affect policy formulation, implementation, and evaluation. The methodology used in this research is qualitative with a focus on literature analysis. Data sources come from several academic works related to post-positivism, constructivism, and public policy in Indonesia. The findings of this study show that while the post-positivist paradigm contributes to the development of a data-driven approach to multiple perspectives, the constructivist paradigm emphasizes the need to understand local social and cultural dynamics in decision-making. Both paradigms are highly effective in producing public policies that are more inclusive and accountable to the needs of the general public. The implication is that Indonesian policymakers should adopt a more critical and contextual approach to policymaking, and improve the application of epistemological principles in the policy development process. This research contributes to the development of philosophy of science discourse in the context of governance, particularly in Indonesia, by offering an alternative perspective to support more effective and successful governance. Keywords: Post-potivism, Constructivism, Public Policy, Philosophy of Science